Which Is The Role of Social Media in Web-Based Adolescent NonSuicidal Self-Injury (NSSI)? - Longo, Giulio; Cavallo, Luciano; Orsolini, Laura; Volpe, Umberto (Journal of Psychology and Psychotherapy Research, 2024)
In recent years, there has been a significant surge in non-suicidal self-injury (NSSI)-related content on the Internet. In fact, the technology landscape rapidly evolved, with social media now playing a pivotal role in the lifestyle of the general population, particularly among youths and adolescents. The current review aims at overviewing all studies so far published investigating the relationship between social media and NSSI among adolescents, focusing on the motivations behind posting NSSI-related contents and the role that social media may play in the promotion and/or maintenance of NSSI behaviors. A comprehensive systematic literature review was carried out by using MEDLINE/PubMed. Following screening through established inclusion criteria, eleven studies were finally selected and here retrieved. Due to the high methodological heterogeneity, all studies were assessed and categorized, based on the type of data collection, in three groups: a) studies using direct data (e.g., interviews/surveys); b) indirect data (e.g., content analysis on social media); and, c) mixed data. Major findings reported that social media may significantly influence the development and maintenance of NSSI behaviors. Those victims of cyberbullying often seek out pro-self-harm contents, to both normalize the behavior and/or seek peer-to-peer emotional support. Social media platforms facilitate the dissemination of self-harm techniques and encourage competition among users, exacerbating the severity of self-injury. Interviews highlighted motivations such as attention-seeking, expressing emotions, and feeling part of a group. Other studies showed that social media contents often contain both supportive and harmful advice regarding self-harm. Social media could cover a dual role in both providing support and triggering self-harm through exposure to harmful content(s). Furthermore, social media could also offer opportunities for positive interventions (i.e., awareness campaigns, mental health resources, etc.). Mental health professionals should be aware about the impact of social media on youngsters, as well as providing a routine assessment on social media use in their clinical practice. Future research should explore the (bi)directional causal role of social media on NSSI and viceversa, as well as developing preventive and treatment strategies to support young people to disincentive NSSI behaviors via social media.